Implementation of a user interface for displaying images with embedded geographical information. - Chiam, Clarence Toon Yao. (2008)
The purpose of this dissertation is to study, explore and design a user interface that is conducive for the management of geocoded images in a map-centric environment. A prototype application was implemented and evaluated as part of the study. Experiences and findings will be also be shared and discussed.